Geographical information ranges: conceptualising holistic information landscapes - Montague, Kaitlin E. (Information Research an international electronic journal, 2025)
Introduction. As unsheltered homelessness is growing in the United States (US), the habitation of vehicles as an affordable housing option is increasing. Policies continue to criminalise and marginalise vehicle residents, pushing them farther away from essential information resources. This study investigates vehicle residency from an information access perspective. Method. Based on six months of ethnographic fieldwork using various methods, this study explores vehicle residents’ information practices, seeking to understand the relationship among vehicle residents, their most utilised resources and the ways that their environments impact their information access. Analysis. Fieldnotes and interview transcripts were analysed using abductive analysis to identify themes and quotations. Visual analysis was used to examine photographs and information horizon maps. Results. Analysis of information horizon maps offer preliminary findings about the ways vehicle residents incorporate their immediate environments and geographical location in their conceptualisations of information and barriers to information access by illustrating natural elements in their information horizon mapping exercises. Conclusions. Geographical location and immediate information environments impact how vehicle residents conceptualise barriers to information access. Gaining a deeper understanding of these understandings and information practices provides theoretical implications for information behaviour research and practical implications for resource development.